Quinoa protein hydrolysates improved the qualities and volatiles of yogurt fermented by Lactobacillus plantarum - Chen, Ao-Xin; Meng, Fan-Bing; Li, Jia-Jia; Chen, Xiao-Chun; Li, Yun-Cheng; Jiang, Li-Shi (Frontiers in Sustainable Food Systems, 2024)
Lactobacillus plantarum is a functional probiotic and could be used in yogurt fermentation to improve the function and flavor. However, L. plantarum has relatively poor acid resistance, and cell viability gradually decreases as pH decreases during yogurt fermentation. Therefore, exploring suitable strategies to promote the fermentation of L. plantarum for yogurt processing is important. In the present study, the effects of quinoa protein hydrolysates (QPHs) on the qualities and volatiles of yogurt fermented by L. plantarum were investigated. QPH addition significantly promoted bacterial growth and organic acids production, subsequently improved the water-holding capacity and viscosity of yogurt. QPH addition also increased the overall antioxidant capacity of yogurt, but the DPPH radical-scavenging ability of 1% QPH-supplemented yogurt was significantly greater than that of 2% QPH-supplemented yogurt. Additionally, QPHs promoted the metabolism of L. plantarum and further promoted the production of volatile flavor compounds. Fifty-two volatile compounds (mainly acids, esters, and ketones) were detected in 2% QPH-supplemented yogurt, which was 1.86-fold greater than the number detected in the control samples. Some aroma components, such as nonanoic acid and maltol, were significantly increased, but undesirable volatiles, such as decanal, were decreased. QPH composition analysis indicated that 60.79% of the peptides contained hydrophobic amino acids at the N-terminus or the C-terminus, which may explain QPHs’ strong antioxidant properties.